2013
DOI: 10.1103/physrevlett.110.143603
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Light Helicity to Nanostructures

Abstract: We discovered that chiral nanoneedles fabricated by vortex laser ablation can be used to visualize the helicity of an optical vortex. The orbital angular momentum of light determines the chirality of the nanoneedles, since it is transferred from the optical vortex to the metal. Only the spin angular momentum of the optical vortex can reinforce the helical structure of the created chiral nanoneedles. We also found that optical vortices with the same total angular momentum (defined as the sum of the orbital and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
136
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(147 citation statements)
references
References 29 publications
2
136
1
Order By: Relevance
“…Later, similar effects were used to produce chiral structures on the surface polymers [12][13][14] and semiconductors [15,16]. Based on their experiments with ablation of bulk tantalum targets [17], the authors revealed that mass transfer and handedness of the produced surface structures are associated with corresponding phase helicity (or OAM), while the polarization helicity (or SAM) accelerates/decelerates the movement of the molten material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, similar effects were used to produce chiral structures on the surface polymers [12][13][14] and semiconductors [15,16]. Based on their experiments with ablation of bulk tantalum targets [17], the authors revealed that mass transfer and handedness of the produced surface structures are associated with corresponding phase helicity (or OAM), while the polarization helicity (or SAM) accelerates/decelerates the movement of the molten material.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a number of papers an alternative pioneering approach, employing optical radiation with specially designed intensity-, polarization-or phase states, was proposed for fabrication of chiral structures [9][10][11][12][13][14][15][16][17][18][19]. In particular, using inherent chirality of nanoparticles, synthesis of twisted nanoribbons through self-assembly in water solution under irradiation with continuous-wave circularly polarized laser radiation was demonstrated * alex.iacp.dvo@mail.ru [9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, helically phased light beams or optical vortices with a field dependence of exp (ilφ), where φ is the azimuthal coordinate and l an integer referred to as the topological charge, are currently among intensively studied topics in optics. These light beams, which carry orbital angular momentum (OAM) [17] that can be transferred to atoms, molecules, and nanostructures [18][19][20][21][22][23], have already been utilized at visible and infrared wavelengths in a wide variety of applications, ranging from micromanipulation [24], detection of spinning objects [25], microscopy [26], and optical data transmission [27][28][29]. Perhaps the most promising applications of vortex beams at short wavelengths are in x-ray magnetic circular dichroism, where different OAM states allow the separation of quadrupolar and dipolar transitions [30], photoionization experiments, where the dipolar selection rules are violated giving rise to new phenomena beyond the standard effect [31], and in resonant inelastic x-ray scattering, where vortex-beam-mediated coupling to vibrational degrees of freedom could provide important information on a wide range of molecular materials [32].…”
mentioning
confidence: 99%
“…The twisted wavefront of an OV suggests that it possesses a well-defined orbital angular momentum (OAM), which was verified in 1992 by Allen et al [1]. Since the validation of the OAM in an OV, numerous promising applications [2][3][4][5][6][7] have been reported. Many studies have been carried out on monochromatic OVs, which have been widely used in the optical manipulation of molecules and nanoparticles [8][9][10].…”
Section: Introductionmentioning
confidence: 93%